Colored flash non-woven fabric as well as preparation method and application thereof
By using high-density polyethylene resin, polyamide resin, maleic anhydride grafted polyethylene and montmorillonite in flash nonwoven fabrics, combining erucic amide to improve the dispersion and compatibility of the toner powder, forming The physical crosslinking network solves the problems of uneven color and easy fall off in the color processing of flash non-woven fabrics, and achieves high intensity, excellent moisture permeability and color stability.
Patent Information
- Application Number
- CN202411205590.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-30
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-08-30
AI Technical Summary
During color processing, existing flash non-woven fabrics are difficult to penetrate and firmly adhere to the ink, which leads to uneven color and easy to fall off. The printing process affects breathable and moisture permeability. After long-term use, the color fades and wears, and the color is introduced during the spinning stage. Powder can damage strength.
Components of colored flash nonwoven fabrics include high-density polyethylene resin, polyamide resin, maleic anhydride grafted polyethylene, montmorillonite and colored masterbatch to improve the dispersion uniformity and phase of the toner powder by erucic amide. Capacitance, forming a physical crosslinking network, improving color stability and moisture permeability.
The high strength, excellent moisture permeability, water resistance and color stability of coloring flash non-woven fabrics are achieved, avoiding the problems of uneven color and easy to fall off, while maintaining the breathability and service life of the product.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and in particular to a colored flash-evaporated nonwoven fabric and a preparation method and application thereof. Background Art
[0002] Flash non-woven fabric is a non-woven fabric material made by flash spinning technology. It has the advantages of high strength, softness, moisture permeability and water resistance.
[0003] Since flash non-woven fabrics have the above-mentioned excellent properties, the application of flash non-woven fabrics is becoming more and more extensive. At the same time, different requirements are also put forward for flash non-woven fabrics. For example, different application fields will have different requirements for color. Existing flash non-woven fabrics are often added and changed by printing process, but on the one hand, due to the special fiber structure and surface properties of flash non-woven fabrics, it is difficult for ink to penetrate evenly and firmly adhere to the fiber surface, resulting in uneven color or easy to fall off. On the other hand, the ink added during the printing process may affect its own air permeability and moisture permeability. On the third hand, during the long-term use of the printed flash non-woven fabric, the ink may gradually fade or wear due to friction, washing and other factors, affecting the appearance and service life of the product. There is also a method in the prior art to introduce color powder in the spinning stage, but this method will cause damage to the strength of the flash non-woven fabric itself.
[0004] Therefore, it is urgent to provide a flash nonwoven fabric that can maintain color for a long time while maintaining good strength, moisture permeability and water resistance. Summary of the invention
[0005] The purpose of the present application is to overcome the shortcomings of the prior art and provide a colored flash-steamed non-woven fabric with good moisture permeability, excellent water resistance, high strength and excellent coloring stability, as well as a preparation method and application thereof.
[0006] To achieve the above object, in a first aspect of the present application, the present application provides a colored flash-steamed nonwoven fabric, the colored flash-steamed nonwoven fabric comprises a colored flash-steamed fiber, and the colored flash-steamed fiber comprises the following components in parts by weight:
[0007] 55-85 parts of high-density polyethylene resin, 10-30 parts of first polyamide resin, 1-8 parts of maleic anhydride grafted polyethylene, 1-4 parts of montmorillonite, and 5-15 parts of masterbatch. The masterbatch includes the following components in parts by mass: 60-90 parts of second polyamide resin, 1-20 parts of color powder, and 1-5 parts of erucic acid amide. The average particle size of montmorillonite is greater than or equal to 1μm and less than or equal to 25μm. The average particle size of the masterbatch is greater than or equal to 0.1μm and less than or equal to 4μm. The grafting rate of maleic anhydride grafted polyethylene is greater than or equal to 0.8% and less than or equal to 1.2%.
[0008] The colored flash-steamed nonwoven fabric provided in the present application is obtained by selecting components in appropriate mass proportions and cooperating with each other, so that the obtained colored flash-steamed nonwoven fabric has excellent moisture permeability, water resistance and high strength, and the obtained colored flash-steamed nonwoven fabric has high stability after coloring.
[0009] Specifically, the present application introduces a color masterbatch, wherein the color masterbatch uses a second polyamide resin as a base resin, and erucic acid amide and a color powder are added at the same time. On the first hand, the introduction of erucic acid amide can not only effectively increase the dispersion uniformity of the color powder in the second polyamide resin, but also improve the compatibility of the color powder and the second polyamide resin, and further improve the stability of the color powder in the second polyamide resin, thereby improving the coloring effect of the color masterbatch. On the second hand, when the color masterbatch is mixed with other raw materials of the colored flash non-woven fabric, erucic acid amide can also cooperate with maleic anhydride grafted polyethylene to further improve the dispersibility of the color powder in the resin matrix and the compatibility with the resin matrix, thereby improving the coloring stability. On the third hand, erucic acid amide can also form a physical cross-linking network with montmorillonite through hydrogen bonding, thereby improving the compatibility and stability of montmorillonite with the resin matrix. At the same time, on the basis of the compatibility and stability of montmorillonite with the base resin, the agglomeration of montmorillonite can be avoided, thereby ensuring the formation of a large number of microporous structures and improving the moisture permeability of the flash non-woven fabric. Fourthly, erucamide can also cooperate with maleic anhydride grafted polyethylene to improve the compatibility between the high-density polyethylene resin, the first polyamide resin and the second polyamide resin, thereby helping to achieve the improvement of the strength, moisture permeability and water resistance of the colored flash-steamed non-woven fabric.
[0010] It should be noted that the average particle size of the masterbatch and the average particle size of montmorillonite are obtained by testing with a laser particle size analyzer.
[0011] Exemplarily, the average particle size of the masterbatch can be any point value or any two point range values between greater than or equal to 0.1μm and less than or equal to 4μm, for example, it can be 0.1μm, 0.2μm, 0.4μm, 0.6μm, 0.8μm, 1.0μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm, 2.0μm, 2.2μm, 2.4μm, 2.6μm, 2.8μm, 3.0μm, 3.2μm, 3.4μm, 3.6μm, 3.8μm, 4.0μm, etc.
[0012] Preferably, the average particle size of the masterbatch is greater than or equal to 1 μm and less than or equal to 2 μm.
[0013] The present application study found that the average particle size of the masterbatch will affect the compatibility and dispersibility of the masterbatch in the resin matrix, thereby affecting the strength, coloring effect and coloring stability of the product. When the average particle size of the masterbatch is further selected to be greater than or equal to 1 μm and less than or equal to 2 μm, the overall effect of the obtained product is better.
[0014] Exemplarily, the average particle size of montmorillonite can be any point value or any two point range values between greater than or equal to 1 μm and less than or equal to 25 μm, such as 1 μm, 3 μm, 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm, 17 μm, 19 μm, 21 μm, 23 μm, 25 μm, etc.
[0015] The present application study found that the average particle size of montmorillonite not only affects the moisture permeability of the product, but also affects the strength of the product. When the average particle size of montmorillonite is further selected to be within the above range, the comprehensive performance of the obtained product is more excellent.
[0016] Preferably, the average particle size of montmorillonite is greater than or equal to 8 μm and less than or equal to 12 μm.
[0017] It should be noted that the grafting rate of maleic anhydride grafted polyethylene is obtained by acid-base titration test.
[0018] For example, the grafting rate of maleic anhydride grafted polyethylene can be any point value or any range value between greater than or equal to 0.8% and less than or equal to 1.2%, such as 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, etc.
[0019] The present application has found that the selection of maleic anhydride grafted polyethylene affects the compatibility of the high-density polyethylene resin and the first polyamide resin, and also affects the compatibility of the high-density polyethylene resin and the color masterbatch. When the grafting rate of maleic anhydride grafted polyethylene is selected within the range given in the present application, a colored flash nonwoven fabric with excellent comprehensive effect can be obtained.
[0020] As a preferred embodiment of the colored flash-steamed nonwoven fabric of the present application, the flash-steamed nonwoven fabric includes the following components in parts by weight: 70 to 80 parts of high-density polyethylene resin, 15 to 20 parts of a first polyamide resin, 4 to 6 parts of maleic anhydride grafted polyethylene, 2 to 3 parts of montmorillonite, and 8 to 12 parts of a color masterbatch.
[0021] The present application study found that the mass fraction of the components of the colored flash-steamed nonwoven fabric will have a significant impact on the comprehensive performance of the product. When the mass fraction of the components of the colored flash-steamed nonwoven fabric is further selected to be within the above range, the comprehensive performance of the obtained colored flash-steamed nonwoven fabric is more excellent.
[0022] As a preferred embodiment of the flash-steamed nonwoven fabric of the present application, the melt index of the high-density polyethylene resin is greater than or equal to 4 g / 10 min and less than or equal to 20 g / 10 min.
[0023] It should be noted that the melt index of high-density polyethylene resin (HDPE) is obtained by testing at 190° C. and 2.16 kg load with reference to ASTM D1238.
[0024] Exemplarily, the melt index of the high-density polyethylene resin can be any point value or any two point range values between greater than or equal to 4 g / 10 min and less than or equal to 20 g / 10 min, such as 4 g / 10 min, 6 g / 10 min, 8 g / 10 min, 10 g / 10 min, 12 g / 10 min, 14 g / 10 min, 16 g / 10 min, 18 g / 10 min, 20 g / 10 min, etc.
[0025] Preferably, the melt index of the high-density polyethylene resin is greater than or equal to 10 g / 10 min and less than or equal to 15 g / 10 min.
[0026] As a preferred embodiment of the colored flash-spun nonwoven fabric of the present application, the first polyamide resin and the second polyamide resin are independently selected from any one of PA6 and PA66.
[0027] As a preferred embodiment of the colored flash-spun nonwoven fabric of the present application, the melt index of the first polyamide resin is greater than or equal to 20 g / 10 min and less than or equal to 35 g / 10 min.
[0028] As a preferred embodiment of the colored flash-spun nonwoven fabric of the present application, the melt index of the second polyamide resin is greater than or equal to 4 g / 10 min and less than or equal to 10 g / 10 min.
[0029] It should be noted that the melt index of the first polyamide resin and the second polyamide resin is obtained by testing at 300° C. and 2.1 kg load with reference to GB / T3682.1.
[0030] Exemplarily, the melt index of the first polyamide resin may be any point value or any two point range values between greater than or equal to 20 g / 10 min and less than or equal to 35 g / 10 min, such as 20 g / 10 min, 22 g / 10 min, 24 g / 10 min, 26 g / 10 min, 28 g / 10 min, 30 g / 10 min, 32 g / 10 min, 34 g / 10 min, 35 g / 10 min, etc.
[0031] Exemplarily, the melt index of the second polyamide resin may be any point value or any two point range values between greater than or equal to 4 g / 10 min and less than or equal to 10 g / 10 min, such as 4 g / 10 min, 6 g / 10 min, 8 g / 10 min, 10 g / 10 min, etc.
[0032] The present application study found that the selection of the melt index of the first polyamide resin and the second polyamide resin will affect the compatibility between the resins and the dispersibility of other components in the resin matrix. When the first polyamide resin and the second polyamide resin are further independently selected as either PA6 or PA66 and the melt index is respectively within the above range, the overall effect of the obtained product is better.
[0033] As a preferred embodiment of the colored flash-steamed nonwoven fabric of the present application, the method for preparing the color masterbatch is as follows: the second polyamide resin, the color powder and erucic acid amide are uniformly mixed, melt-extruded and granulated to obtain the color masterbatch.
[0034] Preferably, the temperature of the melt extrusion is 120-250° C., and the rotation speed is 400-600 rpm.
[0035] As a preferred embodiment of the colored flash-steamed non-woven fabric of the present application, the color powder includes at least one of a benzimidazolone pigment and an isoindolinone pigment.
[0036] The present application has found that when the above-mentioned type of color powder is selected, the problem of poor coloring effect caused by the instability of the color powder itself during the subsequent preparation of the colored flash-steamed non-woven fabric can be avoided.
[0037] Illustratively, the benzimidazolone pigment includes any one of Pigment Brown 25, Pigment Yellow 180, Pigment Yellow 151, Pigment Yellow 183, Pigment Red HF2B, and Pigment Orange HL.
[0038] Illustratively, the isoindolinone pigment includes any one of Pigment Yellow 109, Pigment Yellow 110, Pigment Yellow 138, Pigment Yellow 139, and Pigment Orange 61.
[0039] As a preferred embodiment of the colored flash-steamed nonwoven fabric of the present application, the moisture permeability of the flash-steamed nonwoven fabric is greater than or equal to 4000 g / m according to GB / T12704.1 standard. 2 d and less than or equal to 7000g / m 2 ·d.
[0040] As a preferred embodiment of the colored flash-steamed nonwoven fabric of the present application, the water permeability of the flash-steamed nonwoven fabric according to the GB / T 4744 standard is greater than or equal to 6 KPa and less than or equal to 12 KPa.
[0041] As a preferred embodiment of the colored flash-steamed nonwoven fabric of the present application, the longitudinal breaking strength of the flash-steamed nonwoven fabric is greater than or equal to 100N and less than or equal to 180N according to GB / T 3923.1 standard.
[0042] As a preferred embodiment of the colored flash-steamed nonwoven fabric of the present application, the transverse rupture strength of the flash-steamed nonwoven fabric is greater than or equal to 90N and less than or equal to 170N according to GB / T 3923.1 standard.
[0043] As a preferred embodiment of the colored flash-steamed nonwoven fabric of the present application, the longitudinal elongation at break of the flash-steamed nonwoven fabric is greater than or equal to 14% and less than or equal to 25% according to GB / T 3923.1 standard.
[0044] As a preferred embodiment of the colored flash-steamed nonwoven fabric of the present application, the transverse elongation at break of the flash-steamed nonwoven fabric is greater than or equal to 10% and less than or equal to 22% according to GB / T 3923.1 standard.
[0045] As a preferred embodiment of the colored flash-steamed nonwoven fabric of the present application, the flash-steamed nonwoven fabric has a dry rubbing color fastness of grade 5 and a wet rubbing color fastness of grade 4 to 5 according to GB / T 3923.1 standard.
[0046] In a second aspect of the present application, the present application provides a method for preparing a colored flash-steamed nonwoven fabric, the preparation method comprising the following steps:
[0047] (1) Preparation of spinning solution: Each component is added into a mixing device containing a solvent, and then heated and nitrogen is introduced so that the temperature in the mixing device is greater than or equal to 200° C. and less than or equal to 230° C., and the pressure is greater than or equal to 10 MPa and less than or equal to 12 MPa, to obtain a spinning solution.
[0048] (2) Preparation of flash nonwoven fabric: The spinning solution is placed in a flash spinning device for spinning and received by a receiving device to form a film. The obtained fiber film is cold pressed and hot rolled to obtain a flash nonwoven fabric.
[0049] Preferably, in step (1), the melt extrusion is carried out by using a twin-screw extruder, the screw temperature is 100 to 250° C., and the rotation speed is 400 to 600 r / min.
[0050] Preferably, the boiling point of the solvent is ≤ 100°C.
[0051] More preferably, the solvent includes at least one of benzene, toluene, butane, pentene, n-hexane, heptane, octane, cyclohexane, dichloromethane, carbon tetrachloride, chloroform, chloromethane, chlorofluoromethane, and ethyl chloride.
[0052] More preferably, the mass ratio of the solid phase to the liquid phase in the spinning solution is (10-30):(70-90).
[0053] More preferably, the flash spinning device is prepared using the production equipment 300 used by the inventor in the prior research and development technology CN115323628B.
[0054] It should be noted that the products of the present application are not limited to the production of the above-mentioned production equipment. Technical personnel in this field may also adopt other types of flash production equipment to produce products according to actual needs, as long as products with the same technical characteristics and technical effects can be prepared.
[0055] In the third aspect of the present application, the present application provides the use of flash-steamed nonwoven fabrics in the preparation of decorative materials and daily necessities.
[0056] Preferably, the decorative material includes any one of wall decoration cloth, flower wrapping material, and cultural and creative cover packaging.
[0057] Preferably, the daily necessities include any one of a handbag, a packaging bag, and a seat cover.
[0058] More preferably, the colored flash-steamed nonwoven fabric is combined in the decorative material or daily necessities by at least one of the following methods including but not limited to embedding, bonding or heat sealing, and can be arranged in a certain area or as a whole.
[0059] The flash-steamed nonwoven fabric of the present application has excellent moisture permeability, water resistance, strength and performance, specifically, excellent coloring effect and excellent coloring stability, and can be widely used in decorative materials and daily necessities. While ensuring the moisture permeability and water resistance of the product, it also has good color effect and strength. On the basis of being beautiful, it can be facilitated to quickly distinguish and ensure the service life, that is, it is conducive to practical use.
[0060] Compared with the prior art, this application has the following advantages:
[0061] The colored flash-steamed nonwoven fabric provided by the present application is obtained by selecting components of appropriate mass parts, and the components cooperate with each other. The obtained colored flash-steamed nonwoven fabric has the characteristics of excellent moisture permeability, strong water resistance, high mechanical strength, and high stability of coloring effect. The obtained flash-steamed nonwoven fabric can be effectively applied to the fields of decorative materials and daily necessities. On the basis of meeting the basic moisture permeability and water resistance, it can be effectively distinguished by different colors, and the color durability is excellent. At the same time, on the basis of maintaining a lasting color retention effect, it also has good strength, that is, it can ensure the service life during application. In addition, the raw materials of the colored flash-steamed nonwoven fabric provided by the present application are widely available, and the preparation method is simple to operate, which is conducive to actual production. DETAILED DESCRIPTION
[0062] To better illustrate the purpose, technical solutions and advantages of the present application, the present application will be further described below in conjunction with specific examples. Other materials, reagents, etc. used in the examples, unless otherwise specified, can be obtained from commercial sources.
[0063] HDPE-1: P434350, melt index is 12g / 10min, Aladdin Biochemical Technology Co., Ltd.
[0064] HDPE-2: HMA 014, melt index 4g / 10min, ExxonMobil.
[0065] HDPE-3: HMA 016, melt index 20g / 10min, ExxonMobil.
[0066] Polyamide 1: PA66, EPR 24, melt index 20g / 10min, Shenma Industrial Co., Ltd.
[0067] Polyamide 2: PA6, M2000, melt index 35g / 10min, Guangdong Xinhui Meida Nylon Co., Ltd.
[0068] Polyamide 3: PA66, EPR 32, melt index 8g / 10min, Shenma Industrial Co., Ltd.
[0069] Toner 1: Pigment Red HF2B, commercially available.
[0070] Toner 2: Pigment Orange 61, commercially available.
[0071] Maleic anhydride grafted polyethylene 1: MC509A, maleic anhydride grafting rate 0.8%, Ningbo Nengzhiguang New Materials Technology Co., Ltd.
[0072] Maleic anhydride grafted polyethylene 2: PE-12L, maleic anhydride grafting rate 1.2%, Dongguan Shenghao Plastic Raw Materials Co., Ltd.
[0073] Maleic anhydride grafted polyethylene 3: XUS69109.00, maleic anhydride grafting rate 0.2%, Dow Group, USA.
[0074] Maleic anhydride grafted polyethylene 4: TY 1053H, maleic anhydride grafting rate 2%, Dow Group, USA.
[0075] Montmorillonite 1: The average particle size is 10 μm, homemade.
[0076] Montmorillonite 2: The average particle size is 25 μm, homemade.
[0077] Montmorillonite 3: The average particle size is 1 μm, homemade.
[0078] Montmorillonite 4: average particle size is 30 μm, homemade.
[0079] Montmorillonite 5: The average particle size is 0.1 μm, homemade.
[0080] Erucamide: Commercially available.
[0081] The montmorillonite used was purchased from Tuoyi New Materials (Guangzhou) Co., Ltd. as inorganic montmorillonite, which was then ground, crushed and screened to obtain the corresponding montmorillonites 1 to 5.
[0082] The weight percentages of the color masterbatch components are shown in Table 1.
[0083] Table 1
[0084]
[0085] The preparation method of the masterbatch 1 is as follows: adding the components into a high-speed mixer and mixing them evenly, then melt-extruding and granulating to obtain the masterbatch 1; wherein the temperature of the melt-extrusion is 100-250° C. and the rotation speed is 500 rpm.
[0086] The preparation method of masterbatches 2 to 9 is consistent with that of masterbatch 1; the average particle size can be controlled by the parameters of the granulation process, and then crushed and sieved to obtain masterbatches with corresponding average particle sizes.
[0087] Examples 1 to 13 and Comparative Examples 1 to 9
[0088] The examples and comparative examples of the present application provide a colored flash-steamed nonwoven fabric, and the components (parts by mass) of the colored flash-steamed nonwoven fabric are shown in Tables 2 to 4.
[0089] Table 2
[0090]
[0091]
[0092] Table 3
[0093]
[0094] Table 4
[0095]
[0096]
[0097] The method for preparing the flash nonwoven fabric provided in Example 1 comprises the following steps:
[0098] (1) Preparation of masterbatch: The components are mixed and then transferred into a twin-screw extruder for melt extrusion and granulation at 90-180° C. to obtain the masterbatch. The temperature of the twin-screw extruder is set as follows: 90-110° C. for zone 1, 120-130° C. for zone 2, 150-160° C. for zone 3, 170-180° C. for zone 4, 170-185° C. for zone 5, 170-185° C. for zone 6, 160-165° C. for zone 7, 160-165° C. for zone 8, 160-165° C. for zone 9, and 160-165° C. for zone 10. The screw speed of the twin-screw extruder is 180-220 rpm.
[0099] (2) Preparation of spinning solution: The masterbatch was transferred to a reactor containing a mixed solvent of difluorochloromethane and tetrafluorodichloroethane (15%:85%), preheated to 180°C, then nitrogen was introduced and pressurized to 12 MPa, and finally the temperature was raised to 225°C and stirred in a closed manner for 2 h. After the temperature stabilized, a spinning solution was obtained, in which the mass ratio of the solid phase to the liquid phase was 15:85.
[0100] (3) Preparation of flash nonwoven fabric: Referring to CN115323628B, a flash spinning device 300 was used to transfer the spinning solution to the nozzle for spray spinning, and then the spinning solution was refracted and reflected by a rotating filament separator to form a mesh and laid on a moving mesh curtain. The speed of the ejected air flow was 12000 m / min, the frequency of the rotating filament separator was 35 Hz, and the forward speed of the moving mesh curtain was 45 m / min. The collected mesh was cold pressed at a pressure of 0.5 to 1 MPa and hot rolled at a pressure of 140°C and 3 to 3.5 MPa (the hot rolling roller surface speed was 45 to 50 m / min) to obtain a flash nonwoven fabric with a thickness of about 0.12 mm.
[0101] The preparation methods of the flash-steamed nonwoven fabrics provided in Examples 2 to 13 and Comparative Examples 1 to 9 are consistent with the preparation method in Example 1.
[0102] Effect example
[0103] The effect example of the present application verifies the performance of the colored flash-steamed nonwoven fabrics prepared in Examples 1 to 13 and Comparative Examples 1 to 9, comprising the following steps:
[0104] (1) Moisture permeability: Tested in accordance with GB / T 12704.1.
[0105] (2) Water resistance: Tested in accordance with GB / T 4744 standard.
[0106] (3) Breaking strength and breaking elongation: Tested in accordance with GB / T 3923.1.
[0107] (4) Dry and wet friction color fastness test: The test is carried out in accordance with GB / T3920; in the wet friction color fastness test, the moisture content of the friction cloth is 65%. The color fastness is determined by grades, where grade 1 is the worst and grade 5 is the best.
[0108] The test results are shown in Table 5.
[0109] Table 5
[0110]
[0111]
[0112] It can be seen from Table 5 that when the technical solution provided by the present application is adopted, the obtained colored flash nonwoven fabric has excellent comprehensive performance, large moisture permeability, good water resistance, high breaking strength, excellent elongation at break and strong coloring performance. Specifically, the obtained moisture permeability is 8042~9920g / (m 2 ·d), water permeability between 6.06 and 10.07 KPa, longitudinal breaking strength between 125 and 192 N, transverse breaking strength between 103 and 175 N, longitudinal breaking elongation between 7.1 and 15.0%, transverse breaking elongation between 7.0 and 12.2%, and color fastness test for dry friction of 5 and wet friction of 4 to 5.
[0113] It can be seen from Example 1, Example 8 and Comparative Examples 1-2 that the grafting rate of maleic anhydride grafted polyethylene will affect the performance of the product. When the grafting rate of maleic anhydride grafted polyethylene is not within the range given in this application, the comprehensive effect of the obtained product is significantly reduced. It can be seen from Example 1, Examples 9-10 and Comparative Examples 3-4 that the average particle size of montmorillonite will also affect the comprehensive performance of the product. When the average particle size of montmorillonite is not within the range given in this application, the comprehensive effect of the obtained product is significantly reduced. It can be seen from Example 1, Examples 11-13 and Comparative Examples 5-9 that the color masterbatch will also affect the comprehensive performance of the product.
[0114] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.
Claims
1. A colored flash-steamed nonwoven fabric, characterized in that: The colored flash-steamed nonwoven fabric comprises colored flash-steamed fibers, and the colored flash-steamed fibers comprise the following components in parts by weight: 55-85 parts of high-density polyethylene resin, 10-30 parts of first polyamide resin, 1-8 parts of maleic anhydride grafted polyethylene, 1-4 parts of montmorillonite, and 5-15 parts of color masterbatch; The color masterbatch comprises the following components in parts by weight: 60 to 90 parts of a second polyamide resin, 1 to 20 parts of a color powder, and 1 to 5 parts of erucamide; The average particle size of the montmorillonite is greater than or equal to 1 μm and less than or equal to 25 μm; The average particle size of the masterbatch is greater than or equal to 0.1 μm and less than or equal to 4 μm; The grafting rate of the maleic anhydride grafted polyethylene is greater than or equal to 0.8% and less than or equal to 1.2%.
2. The flash-steamed nonwoven fabric according to claim 1, characterized in that: The flash nonwoven fabric comprises the following components in parts by weight: 70-80 parts of high-density polyethylene resin, 15-20 parts of first polyamide resin, 4-6 parts of maleic anhydride grafted polyethylene, 2-3 parts of montmorillonite, and 8-12 parts of color masterbatch.
3. The flash-steamed nonwoven fabric according to claim 1, characterized in that: The melt index of the high-density polyethylene resin is greater than or equal to 4 g / 10 min and less than or equal to 20 g / 10 min.
4. The flash-steamed nonwoven fabric according to claim 1, characterized in that: The first polyamide resin and the second polyamide resin are independently selected from any one of PA6 and PA66; And / or, the melt index of the first polyamide resin is greater than or equal to 20 g / 10 min and less than or equal to 35 g / 10 min; And / or, the melt index of the second polyamide resin is greater than or equal to 4 g / 10 min and less than or equal to 10 g / 10 min.
5. The flash-steamed nonwoven fabric according to claim 1, characterized in that: The toner includes at least one of a benzimidazolone pigment and an isoindolinone pigment.
6. The flash-steamed nonwoven fabric according to claim 1, characterized in that: The preparation method of the color masterbatch is as follows: the second polyamide resin, the color powder and erucic acid amide are uniformly mixed, melt-extruded and granulated to obtain the color masterbatch.
7. The flash-steamed nonwoven fabric according to claim 1, characterized in that: The moisture permeability of the flash nonwoven fabric is greater than or equal to 4000 g / m according to GB / T12704.1 standard. 2 d and less than or equal to 7000g / m 2 ·d; And / or, the water permeability of the flash-steamed nonwoven fabric according to GB / T4744 standard is greater than or equal to 6 KPa and less than or equal to 12 KPa; And / or, the longitudinal breaking strength of the flash-steamed nonwoven fabric is greater than or equal to 100N and less than or equal to 180N according to GB / T 3923.1 standard; And / or, the transverse rupture strength of the flash-steamed nonwoven fabric is greater than or equal to 90N and less than or equal to 170N according to GB / T3923.1 standard; And / or, the longitudinal elongation at break of the flash-steamed nonwoven fabric is greater than or equal to 14% and less than or equal to 25% according to GB / T3923.1 standard; And / or, the transverse elongation at break of the flash-steamed nonwoven fabric is greater than or equal to 10% and less than or equal to 22% according to GB / T3923.1 standard; And / or, the flash-steamed nonwoven fabric has a dry rubbing color fastness of grade 5 and a wet rubbing color fastness of grade 4-5 according to GB / T3923.1 standard.
8. The method for preparing a flash-steamed nonwoven fabric according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) Preparation of spinning solution: adding each component into a mixing device containing a solvent, then heating and introducing nitrogen so that the temperature in the mixing device is greater than or equal to 200° C. and less than or equal to 230° C., and the pressure is greater than or equal to 10 MPa and less than or equal to 12 MPa, to obtain a spinning solution; (2) Preparation of flash nonwoven fabric: The spinning solution is placed in a flash spinning device for spinning and received by a receiving device to form a film. The obtained fiber film is cold pressed and hot rolled to obtain a flash nonwoven fabric.
9. Use of the flash-steamed nonwoven fabric according to any one of claims 1 to 7 in the preparation of decorative materials and daily necessities.
10. The use according to claim 9, characterized in that: The decorative material includes any one of wall decoration cloth, flower wrapping material, and cultural and creative cover packaging; And / or, the daily necessities include any one of a handbag, a packaging bag, and a seat cover.
Citation Information
Patent Citations
Antistatic flash-spun composite nonwoven fabric and preparation method thereof
CN115323628B
Grounded electrical connector
US6910900B2
Preparation method of high-density polyethylene / polyamide 66 laminar barrier materials using in-situ reactive compatibilization method
CN102786633A
Halogen-free flame-retardant environment-friendly covered polyolefin yarn fabric and preparation method thereof
CN104233569A
Polyamide composite material and preparation method thereof
CN104725839A